2013
DOI: 10.1136/emermed-2013-202794
|View full text |Cite
|
Sign up to set email alerts
|

Regional analgesia in the emergency department for hip fractures: survey of current UK practice and its impact on services in a teaching hospital

Abstract: RA for HFs is not widely used in UK EDs, proving that there is room for improvement .The finding that RA blocks are performed by the ED medical staff in 84% of the responding EDs practising RA was reassuring for developing the service in our hospital. FICB should be considered as an alternative to parenteral analgesia in adult patients with HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
0
18
1
Order By: Relevance
“…10,11 Up to 84% of emergency departments in the UK use regional anaesthesia for hip fracture patients; FICB is the first-line regional anaesthesia. 5 This has led to the introduction of a nurse-led FICB service for patients with femoral neck fracture. [12][13][14] The analgesic reliability of FICB has led to its introduction in the pre-hospital setting in some countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…10,11 Up to 84% of emergency departments in the UK use regional anaesthesia for hip fracture patients; FICB is the first-line regional anaesthesia. 5 This has led to the introduction of a nurse-led FICB service for patients with femoral neck fracture. [12][13][14] The analgesic reliability of FICB has led to its introduction in the pre-hospital setting in some countries.…”
Section: Resultsmentioning
confidence: 99%
“…15 Bupivacaine has been used to investigate the analgesic effect of FICB. [3][4][5][7][8][9][10][11][12][13] It has a rapid onset (2-5 minutes), 16,17 with the maximum plasma level occurs after 15 to 30 minutes. 18 It has fewer toxic reactions relative to lidocaine, 19 with a half-life of 157 minutes, 20 and its local anaesthetic effect lasts for up to 8 hours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One small study actually demonstrated feasibility in pre-hospital settings, 13 but regional anaesthesia is not commonly used in the contemporary ED. 14,15 Dr. Chris Carpenter posed the question of how to learn to perform ultrasound-guided nerve blocks and asked about the learning curve for the procedure. Drs.…”
mentioning
confidence: 99%